Análisis documental de factores que influyen en el uso de prótesis dental en el adulto mayor para la elaboración de un formato de seguimiento en clínica. (2020)
Objective. Gather the information that allows strengthening the tools to extend the duration of physical well-being of the elderly that improves their quality of life by overcoming the factors that influence the use of prostheses Methodological design. Documentary analysis, within a qualitative approach Results. Authors such as Pennacchioti, Vanegas, Cirilo, Rueda, Saez, Monroy and Navarro, have shown that the factors that influence use are directly related to the state and condition of the elderly and the use and care of prostheses Conclusions. The studies analyzed and presented allow us to answer the research question about which factors influence the use of dental prostheses in the elderly, described from the factors associated with the state and condition of the elderly, which confirm that the use of prostheses is directly related to social, economic and demographic factors